الاسرة الحسينية بتونس والقرمانلية بطرابلس الغرب (عهد التاسيس و المواقف) 1705-1745م - - تركي، سمية, ذيب، سناء (جامعة الوادي University of eloued, 2018)
"الملخص: إن ظهور الأسرتين الحسينية بتونس و القرمانلية بطرابلس الغرب بداية القرن الثامن عشر وحتى منتصف القرن التاسع عشر كان لذلك جملة من الظروف والعوامل التي جعلتهما كقوة محلية من خلالها تم إنهاء الحكم العثماني المباشر الذي دام من( 1541-1705م)بتونس و (1551-1711م) بطرابلس الغرب ، مع بقاء فرمانات التولية ، لأنهما ظلتا تابعتين للدولة العثمانية. كلا الأسرتين كولوغلي تركي قدما إلى كل من تونس و طرابلس الغرب استوطنوا وامتزجوا مع الأهالي وشكلوا صنف جديد يعرف بالكولوغلي , واندمجوا حتى أصبحوا لا يميزون عن السكان الأصليين . و سبق تأسيس كلا الأسرتين ظروفًا وأحداثًا أدت لوصولهما لكرسي الحكم وإنهاء الحكم التركي وتأسيس دولتين مستقلتين ذاتيا عن الباب العالي تابعتان له اسميا ، بالنسبة لأيالة تونس فقد عاشت فترة انتقالية من سنة 1702مإلى سنة 1705م هذه الفترة كانت تحت حكم إبراهيم الشريف , بينما طرابلس الغرب كانت تحت حكم عثماني يتمثل في فترة حكم الدايات التي تميزت بالضعف والاضطرابات . وقد عمل كل من أحمد بك و الحسين بن علي إنهاء تسلط الانكشارية وإبعادهم عن الحكم بالقتل أو إعطائهم مناصب اسمية رمزية . و تمت لكل منهما البيعة من قبل الأهالي والجند الذين رأوا فيهما أنهما الأصلح وأنهما سيخلصان البلاد من الفوضى والاضطراب . كان لكل من أحمد بك وحسين بن علي إهتمامات بشتى المجالات وكانت لهما أعمال في الجوانب المختلفه سياسيا واقتصاديا وعمرانيا.. بقيت هذه الاعمال شواهد على جهودهما للقيام بالبلاد في أحسن صورة. كان لتأسيس الأسرتين الحسينية بتونس و القرمانلية بطرابلس الغرب مواقف عده سواء كانت على الصعيد الداخلي أو الخارجي، كانت بين موالي لهما ومعارض. ففي ضل حكم المؤسسين بإيالة تونس و طرابلس الغرب ظهرت عدة اضطرابات و تمردات، فإيالة تونس كثر بها الطامعون والمناوئون للسلطة، فكانت الحرب الأهلية التي جرت بالبلاد إلى انقسامات وصراعات داخلية . أما طرابلس الغرب فنتيجة لتسلط أحمد القرمانلي وجوره في إثقال كاهل السكان بالضرائب جعلهم يتمردون وساعدهم على ذلك طبيعتهم التي لا تنقاد لحكم شخص دون سيد القبيلة. أما الباب العالي فقد كانت علاقة الإيالتين به علاقة تبعية اسمية تمثلت في فرمانات التولية و أداء فروض الطاعة من هدايا و هبات الترضيات و المساعدة أثناء الحروب وذلك لانشغالها في حروبها مع الروس و الألمان و غيرها من الدول الأوروبية. أما علاقة الإيالتين ببعضهما فسادها التوتر تارة و الانفراج تارة أخرى بسبب مشكل الحدود، و كانت إيالة الجزائر كثيرة التدخل في شؤون تونس وحاولت إبقاء تونس تابعة لها هذا من جهة ، و نسجل أحيانا من جهة أخرى تحالف تونس و طرابلس الغرب للحد من تدخلات إيالة الجزائر في شؤونهما. أما بالنسبة لدول الأوروبية فقد حرص كل مؤسس للأسرة على إقامة علاقات طيبة مع فرنسا و الجمهوريات الإيطالية، و بموجب الامتيازات الممنوحة لها فتح المجال أمام الدول الأوروبية لتظهر أطماعها التوسعية في الأيالات. " ABSTRACT: The emergence of the Husseini families in Tunis and Qarmanlya in Tripoli from the beginning of the eighteenth century until the middle of the nineteenth century was a set of circumstances and factors that made them a local force through which the Ottoman rule was terminated directly from (1541-1705) in Tunisia and (1551-1711) In Tripoli West, with the survival of the Fermanat Altolip, because they remained the Ottoman Empire. Both the Kulugli families moved forward to Tunisia and Tripoli West settled and merged with the people and formed a new class known as Kulogli, and merged until they do not distinguish from the indigenous people . The two families have already established conditions and events that led to their accession to the throne and the end of the Turkish rule and the establishment of two independent states from the Supreme Gate followed by nominally. For the Eyala of Tunisia, it lived a period of transition from 1702 to 1705. This period was under Ibrahim al-Sharif, Ottoman rule is the rule of the daiyat which was characterized by weakness and unrest. Both Ahmed Bey and Hussein bin Ali worked to end the Ansarism and to distance them from the government by killing them or giving them nominal symbolic positions. And the allegiance of both parents and soldiers who saw them as the best and that they will save the country from chaos and turmoil. Both Ahmed Bey and Hussein Bin Ali had interests in various fields and had work on various aspects politically, economically and academically. These works remained proof of their efforts to do the country in the best possible way. The establishment of the Husseini families in Tunisia and the Qaramania in Tripoli, the West, had a number of positions, whether internal or external, between their supporters and opponents. Under the rule of the founders of the Nile, Tunisia and Tripoli in the West, there have been many riots and rebellions. Tunisia has a large number of oppressors and opponents of power. The civil war that took place in the country led to internal divisions and conflicts. As for Tripoli in the West, Ahmed Qormanli and Joura took the burden of taxes on the people and made them rebel, aided by their unquestioned nature of the rule of a man without the master of the tribe. As for the higher gate, the relationship between the two was a nominal dependency relationship, which was in the formations of the Tolle and the performance of the duties of obedience of gifts and gifts of gratifications and assistance during the wars for the preoccupation in the wars with the Russians and Germans and other European countries. As for the relationship between the two countries, their corruption is sometimes tempered by the problem of borders. Algeria has been very involved in the affairs of Tunisia and has tried to keep Tunisia affiliated with it. On the one hand, we are sometimes recording the alliance of Tunisia and Tripoli in order to limit the interference of Algeria. Their affairs. As for the European countries, each founder of the family was keen to establish good relations with France and the Italian republics, and under the privileges granted to them, opened the way for European countries to show their ambitions expansionist in the elephants.
دراسة مقارنة
المغرب العربي الوسيط والحديث مذكرة ماستر تاريخ تخصص تاريخ
Keywords: "الكلمات المفتاحية: الأسرة الحسينية، الاسرة القرمانلية ،تأسيس ،المواقف، حسين بن علي ،أحمد بك القرمانلي; "Mots-clés: Husseiniya Family, Qarmanliya Family, Founding, Attitudes, Hussain Ben Ali, Ahmed Bak Al-Qormanli "; Husseiniya Family, Qarmanliya Family, Founding, Attitudes, Hussain Ben Ali, Ahmed Bak Al-Qormanli